Understanding the physician - Owen, Mike (Henry Stewart Talks, 2009)
The world of the physician and the role that research can play in uncovering this world, Understanding the beliefs and motivations of the physician, Approaches and techniques that help us explore the beliefs and motivations of physicians, Analysis and interpretation of the information we gather, Using our research to help market brands more effectively